Educational Science Learning Activities For Early Childhood At RA Al-Hajjah - Yusnita, Novi Cynthia; Aisyah, Dara; Nisa, Khairatun (Outline Journal of Community Development, 2026)
Science learning is a fun way for early childhood. Science can be defined as something that stimulates curiosity, interest, problem-solving, and leads to thinking and action, such as reflection, the relationship between concepts and events, and observation. However, what happens in the field is that children sometimes feel bored during the learning process in the classroom. This occurs because the methods or media used by teachers do not attract children's interest in participating in the learning process. This community service activity was carried out with the aim of attracting children's interest in learning so that all aspects of their development can run optimally. The methods used in this community service were experiments, play, and question and answer. This community service activity was carried out at RA Al-Hajjah, Percut Sei Tuan District, with a total of 23 children. After this community service activity, the children became more enthusiastic about the learning process. Children also practiced their critical thinking skills in problem-solving. This can also serve as a reference for teachers to make learning more enjoyable and creative.